2020
DOI: 10.2298/tsci180903010d
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimum insulation thickness for building external walls with different insulation materials using environmental impact assessment

Abstract: The aim of this study is to determine the optimum heat insulation thickness for the glasswool and rockwool insulation material. Since natural gas is mostly used for heating in Turkey, it has been selected as fuel for the calculation. In order to calculate the optimum thickness of the insulation, the number of the degree-day and total environmental factor have been used. For the optimum insulation thickness, the decrease in exergy loss, CO2 emission and the fuel consumption were 75%, 73%, and 71% for the glassw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…Later on, Aydın and Bıyıklıoğlu [14] presented that the energy savings achieved by optimum insulation thicknesses determined by life cycle cost analysis (LCCA) varies between 12.9% and 21.5% depending on the degree-day regions. In another study on insulation thickness, it was found that optimum thickness glass wool and rockwool insulation materials reduce fuel consumption by approximately 70% and 40% [15]. According to Ozalp et al [16], the effect of wall building material on heat losses is much higher than insulation material.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, Aydın and Bıyıklıoğlu [14] presented that the energy savings achieved by optimum insulation thicknesses determined by life cycle cost analysis (LCCA) varies between 12.9% and 21.5% depending on the degree-day regions. In another study on insulation thickness, it was found that optimum thickness glass wool and rockwool insulation materials reduce fuel consumption by approximately 70% and 40% [15]. According to Ozalp et al [16], the effect of wall building material on heat losses is much higher than insulation material.…”
Section: Introductionmentioning
confidence: 99%
“…Kullanılan nicel hesaplamalar sayesinde binalar bazında yalıtım kalınlığı bakımından en uygun değerin bulunması ve en tasarruflu yakıt tipinin seçilmesi işlemleri gerçekleştirilebilmektedir. Binalardaki ısı kayıplarının genel olarak pencere açıklıklarından, tavan aralıklarından ve hava akımları etkisiyle oluştuğu birçok araştırmacı tarafından belirtilmiştir [20,21,22]. Bu çalışmada yapılan hesaplamalar sadece dış duvarlardan ısı kaybı olduğu kabul edilerek gerçekleştirilmiştir.…”
Section: Materyal Ve Metod (Materials Andunclassified
“…By the end of 2021, the proportion of energy-efficient buildings to the existing building area in the south of China was only 23.1%, and the heating and cooling energy consumption per unit area was equivalent to more than two times that of developed countries with similar latitudes [2] , which was mainly due to the poor thermal insulation performance of the building envelope in the high humidity environment in the south. As shown in Figure 1, the building envelope (mainly refers to the external wall) is composed of insulation materials and wall materials composite [3][4][5] . At present, the vast majority of building envelope in China adopts external wall exterior insulation or external wall interior insulation technology.…”
Section: Introductionmentioning
confidence: 99%